Effectiveness of either short-duration ischemic pre-conditioning, single-set high-resistance exercise, or their combination in potentiating bench press exercise performance - Salagas, Andreas; Tsoukos, Athanasios; Terzis, Gerasimos; Paschalis, Vassilis; Katsikas, Christos; Krzysztofik, Michal; Wilk, Michal; Zajac, Adam; Bogdanis, Gregory C. (Frontiers in Physiology, 2022)
This study compared the effects of short-duration ischemic preconditioning, a single-set high-resistance exercise and their combination on subsequent bench press performance. Twelve men (age: 25.8 ± 6.0 years, bench press 1-RM: 1.21 ± 0.17 kg kg−1 body mass) performed four 12 s sets as fast as possible, with 2 min of recovery between sets, against 60% 1-RM, after: a) 5 min ischemic preconditioning (IPC; at 100% of full arterial occlusion pressure), b) one set of three bench press repetitions at 90% 1-RM (PAPE), c) their combination (PAPE + IPC) or d) control (CTRL). Mean barbell velocity in ischemic preconditioning was higher than CTRL (by 6.6–9.0%, p < 0.05) from set 1 to set 3, and higher than PAPE in set 1 (by 4.4%, p < 0.05). Mean barbell velocity in PAPE was higher than CTRL from set 2 to set 4 (by 6.7–8.9%, p < 0.05), while mean barbell velocity in PAPE + IPC was higher than CTRL only in set 1 (+5.8 ± 10.0%). Peak barbell velocity in ischemic preconditioning and PAPE was higher than CTRL (by 7.8% and 8.5%, respectively; p < 0.05). Total number of repetitions was similarly increased in all experimental conditions compared with CTRL (by 7.0–7.9%, p < 0.05). Rating of perceived exertion was lower in ischemic preconditioning compared with CTRL (p < 0.001) and PAPE (p = 0.045), respectively. These results highlight the effectiveness of short-duration ischemic preconditioning in increasing bench press performance, and suggest that it may be readily used by strength and conditioning coaches during resistance training due to its brevity and lower perceived exertion.